JURNALISME GAME DAN MEMBAURNYA KARAKTER KONTEN MEDIA: Studi Kasus the Lazy Monday, Gamebrott dan Playverse - Adiputra, Wisnu Martha (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2018)
Game journalism develops along with the development of the gaming industry, increasingly sophisticated information and communication technology, as well as increasingly convergent institutionalization of new media. The purpose of this research is to understand game specialist journalism and blend the study of content production. The research method used is a case study with a constructionist perspective. Data collected through interview, content review, and literature review related to journalism, games, and the media industry. The mixed character of the media content in game news is, among others, reviewed through media institutions, media practices, namely: planning, management, production and distribution, and through dimensions in journalism. To cite this article (7th APA style): Adiputra, W. M. (2018). Jurnalisme Game dan Membaurnya Konten Media: Studi Kasus the Lazy Monday, Gamebrott dan Playverse [Game Journalism and the Immersion of the Media Content Character]. Journal Communication Spectrum, 8(2), 166-189. http://dx.doi.org/10.36782/jcs.v8i2.1853